Bound the peoples by her fate: the Kabardian princess and the Kalmyk khansha Janet - L. J. Kokova; B. J. Kokova (Nomadic Civilization: Historical Research)
The object of the article is the identity of the Kalmyk khansha Dzhan, a Kabardian by nationality, the second wife of the Kalmyk khan Donduk-Ombo. The image of Janet in these different guises has forever remained in the historical memory of the two peoples, becoming an iconic symbol of a certain era. It was and remains a “bridge” connecting different peoples and cultures. In the proposed article, historically, the life path of the Kalmyk khansha Dzhan is explored, her place in the history of Russia, the Kalmyk Khanate is comprehended, an assessment is made of the role of this outstanding womanin building the initial Kabardino-Kalmyk relations. The relevance of such a study is due to the need to show a comprehensive, holistic, integral history of the Kalmyk people in the pre-revolutionary period. The authors raise the topic of the role of women in political life in the past, her place in the everyday life of the Kalmyks of that time. After the death of her husband, remaining a widow, she went along with the Kalmyk people who became her native people, a difficult, martyr’s path.   The purpose and objectives of the study are to reveal the tragic fate of this outstanding personality through the study of direct and indirect connections with his contemporaries, ancestors, descendants, the Russian Empire, the history of the Kabardian and Kalmyk peoples.   The authors explore historically the image of the Kalmyk khansha Dzhan, relying on the descriptions of Russian historians, trying to comprehend her role and place in the history of the Kalmyk people. The relevance of such a study is undeniable. The article lifts the veil of secrecy over the personality of the khansha and adds new touches to her historical portrait. In historical and genetic terms, against the background of Kabardian-Circassian and Russian parallels in the history of the origin of double surnames, the origin of the legendary Kabardian surname of Princess Janet Kurgokina (Atazhukina) is considered. The article presents the genealogy of the Dondukov-Korsakov family, the ancestor of which was the Kalmyk khansha, the widow of the Kalmyk khan Donduk-Ombo, who later became Princess Vera Dondukova by royal command. The Dondukov-Korsakov clan has a wide branching, is represented by famous names that glorified Russia with military, labor and public affairs.